Pengaruh Intellectual Capital, Komite Audit, Komisaris Independen Terhadap Integritas Laporan Keuangan - Difa Raiza Herlambang; Annisa Nurbaiti (Politeknik Ganesha Medan, 2023)
A good financial report is a report that contains the company's condition accurately. The integrity of financial reports is a report that presents financial information in a fair, honest and impartial manner. This learning benchmark is an examination of the impact of intellectual capital, the Audit Committee, and the Independence of the Board of Commissioners regarding the Integrity of Financial Statements. This study uses a sample size of 45 information units from the transportation and logistics sector of nine companies listed on the Indonesia Stock Exchange. during the period 2017 to 2021 as research subjects. This analysis uses a quantitative approach which is based on a deliberate purposive sampling technique for selecting the sample. Information analysis was performed through information panel regression, and information checking was performed using eviews 12. Descriptive statistics, classic firm assumption testing and hypothesis testing using the regression model for the information panels were used. Based on the results of this study indicate that intellectual capital. The audit committee and the independence of the board of commissioners have an effect simultaneously. Meanwhile, the results of a partial examination of the committee and the independence of the board of commissioners have no effect on the integrity of financial reports, while intellectual capital has an effect on the integrity of financial statements.